Human Involvement In Association Rule Mining: The Role of Human Heuristics in Association Rule Mining (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Anumber of data mining algorithms have been introduced to the community thatperform summarisation and classification of data with respect to a targetattribute, deviation detection, and other forms of data characterisation andinterpretation. One popular summarisation and pattern extraction algorithm isthe association rule algorithm. Association rule is described as anassociational relationship between a group of objects in a transactionaldatabase [Zhang S. et.al., 2006]. The following discussion shall be useful toJustify the intervention of human heuristics in the data mining process.